Chinese Consumers’ Herd Consumption Behavior Related to Korean Luxury Cosmetics: The Mediating Role of Fear of Missing Out - Kang, Inwon; He, Xue; Shin, Matthew Minsuk (Frontiers in Psychology, 2020)
Many news and articles report Chinese consumers’ lavish and collective spending spree on Korean luxury cosmetics brands. This study aims to examine root causes of Chinese consumers’ collective stockpiling consumption on certain luxury brands. This study assumes that ‘fear of missing out (FoMO)’ as Chinese consumers characteristics that lead to their collective stockpiling consumption. To gain psychological comfort, consumers with high FoMO may be prone to develop high brand involvement leading to their collective consumption on the luxury brands. In consumer studies, such collective consumption behavior is referred to as herd behavior. Thus, the main research question of this study is “why do Chinese consumers show herd consumption behavior toward certain luxury brands?” Then, the proposition made in this study is that among consumers with relevant characteristics of being more attracted to luxury brands, those with high FoMO will develop higher involvement into the luxury brand and the involvement will lead to their herd consumption behavior toward the brand. To validate this proposition, this study surveyed Chinese consumers. The collected data was analyzed by structural equations modelling method using SPSS and AMOS. Based on the results, this study offers theoretical explanations of why Chinese consumers make such collective obsession-like stockpiling consumption on certain luxury brands and offers managerial implications regarding this phenomenon.